Impacts émancipateurs d’une coopération scientifique-enseignant à l’école primaire sur les représentations des enfants et leur mobilisation dans les apprentissages en sciences - Marie Odile Lafosse-Marin (Recherches en Éducation)
Does a science education in which a scientific student cooperates with a school teacher increase the emancipation of the pupils ? The impacts of this practice on children's learning are studied through linguistic interactions in science sessions at primary school. The representations built by girls and boys are analyzed through 1500 captioned pictures drawn by third cycle pupils. Various factors emerge : emancipation from a subjugation to a definite type of knowledge ; freeing both from being assigned to a definite location in the classroom and from the permanent control of the teacher ; release from confining social representations. The multifaceted and interactive dynamics between the teacher, the accompanying student and the pupils act in a circular scheme which does emancipate the teaching, the knowledge and the learning. The pupils are more open to respond and to agree to a teaching program proposed by the teacher-student binomial, than imposed by the teacher alone : they adopt new learning postures. Unprecedented motivation follows by identification with the young scientist. It leads also to emancipation from self-censorship related to stereotypes. This presses specially on girls, and disadvantaged children sometimes deprived from Science lessons, because so-called fundamentals "reading, writing and computing" would be more important.